The evidence for the top quark : - Staley, Kent W. (Cambridge University Press, 2004)
Offering an historical and philosophical perspective on an important recent discovery in particle physics, the first evidence for the elementary particle known as the top quark, this study draws on published reports, oral histories, and internal documents. Kent Staley explores in detail the controversies and politics that surrounded the major scientific result. His book defends an objective theory of scientific evidence based on error probabilities.